L’offre alimentaire urbaine face au défi de la diffusion des supermarchés. Regards croisés sur Rio de Janeiro et Brasilia - Emília de Medeiros Silva Jomalinis; Juscelino Eudâmidas Bezerra; Ève Anne Bühler (Confins)
In a context of rising food insecurity and undermining of food policies in Brazil, large-scale retailers continue to grow and are capturing a larger proportion of market share. The article reviews these recent trends and then proposes a characterization of the dynamics of mass distribution of food in two national metropolises, Rio de Janeiro and Brasilia, important consumption centers and hotbeds of the breakthrough of multinational retail groups. These case studies shed light on the profiles of the main groups involved, their localization strategies and marketing segmentation related to the socio-economic characteristics of the population, and food and nutrition security.